Aptamer-engineered extended-gate field-effect transistor device for point-of-care therapeutic drug monitoring. Issue 20 (23rd September 2022) - Zhang, Mengyang; He, Junqing; Zheng, Youbin; Shi, Guoyue; Zhang, Min
Abstract : A portable point-of-care testing (POCT) device based on an aptamer-engineered extended-gate field-effect transistor (EG-FET) was unveiled for therapeutic monitoring of the drug methotrexate. Abstract : Herein, we report a portable point-of-care testing (POCT) device based on an aptamer-engineered extended-gate field-effect transistor (EG-FET) for therapeutic monitoring of the drug methotrexate. This method was shown to be highly sensitive, efficient, and convenient to use, features contributing to its realizing a clinical detection of drugs in blood.